Comorbidity Index as a Predictor of Mortality in Pediatric Patients With Solid Tumors - Luz María Torres-Espíndola; Joel Demetrio-Ríos; Liliana Carmona-Aparicio; César Galván-Díaz; Martín Pérez-García; Juan Luís Chávez-Pacheco; Julio Granados-Montiel; Israel Torres-Ramírez de Arellano; Arnoldo Aquino-Gálvez; Manuel De Jesús Castillejos-López (Frontiers Media S.A., 2019)
Purpose: The objective of this study was to determine whether a comorbidity index could be used to predict mortality in pediatric patients with chemotherapy-treated solid tumors.Methods: Pediatric patients who underwent chemotherapy treatment for solid tumors were included, and demographic, clinical, and comorbidity data were obtained from patient electronic records.Results: A total of 196 pediatric patients with embryonic solid tumors were included. Metastatic tumors were the most frequently observed (n = 103, 52.6%). The most common comorbidities encountered for the Charlson comorbidity index (CCI) were cellulitis (n = 24, 12.2%) and acute renal failure (n = 15, 7.7%). For the Pediatric Comorbidity Index (PCI), the most frequent comorbidities were pneumonia and sepsis, with n = 64 (32.7%) for each. We evaluated established the prognostic values for both indexes using Kaplan-Meier curves, finding that the CCI and PCI could predict mortality with p < 0.0001.Conclusion: Using the PCI, we observed 100% survival in patients without comorbidities, 70% survival in patients with a low degree of comorbidity, and 20% survival in patients with a high degree of comorbidity. Greater discrimination of probability of survival could be achieved using degrees of comorbidity on the PCI than using degrees of comorbidity on the CCI. The application of the PCI for assessing the hospitalized pediatric population may be of importance for improving clinical evaluation.